WORKSHOP PEMBUATAN PODCAST UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KREATIVITAS ERA DIGITAL MAHASISWA POLITEKNIK KESEHATAN KALTARA DI UNIVERSITAS BORNEO TARAKAN - Kharis Hudaiby Hanif; Nurul Audryan; Bisma Baghas Waluyo; Putri Maimunah; Nurul; Andi Zilvia Ayu Ardina; Muhammad Akmaluddin (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
Podcasts are a digital platform that plays an important role in disseminating information, especially in the field of health promotion. This community service program aims to increase the knowledge and skills of North Kalimantan Health Polytechnic students in using podcasts as a medium to convey health messages. Challenges faced in this activity include a lack of understanding of podcast creation techniques, and a lack of knowledge regarding the benefits in disseminating health information. This service is carried out using the following methods: 1) Presentation of material about making podcasts, 2) practical training in recording podcasts, and 3) teaching about the operation of technical devices such as microphones and editing software. The results achieved from this activity are an increase in students' ability to produce and create effective podcasts, as well as a better understanding of the importance of podcasts in disseminating health information to the public. This program also produces content that can be accessed by various groups.